2019
DOI: 10.1080/19440049.2019.1654139
|View full text |Cite
|
Sign up to set email alerts
|

Verification and evaluation of monochloropropanediol (MCPD) esters and glycidyl esters in palm oil products of different regions in Malaysia

Abstract: This study was conducted to investigate on the effect of different sampling regions of palmrefined oils and fats on the 2-and 3-monochloropropanediol fatty acid esters (MCPDE) and glycidol fatty acid esters (GE) levels. The American Oil Chemists' Society (AOCS) Official Method Cd 29a-13 on the determination of MCPDE and GE in edible oils and fats by acid transesterification was successfully verified and optimised, with slight modification using 7890A Agilent GC system equipped with 5975C quadrupole detector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Among the variable contents of 3-MCPD esters, palm oils analyzed with a modified indirect analytical method were reported with the greatest level at 9647 μg/kg compared to other vegetable oils (from not detectable to 4224 μg/kg) in Taiwan . Similar results were also reported in palm oils collected from Malaysia , and Spain . Furthermore, blended oils containing palm oil were also accompanied by greater levels of MCPD esters and glycidyl esters (GEs) against other oils .…”
Section: Recent Occurrences In Foodstuffssupporting
confidence: 79%
See 2 more Smart Citations
“…Among the variable contents of 3-MCPD esters, palm oils analyzed with a modified indirect analytical method were reported with the greatest level at 9647 μg/kg compared to other vegetable oils (from not detectable to 4224 μg/kg) in Taiwan . Similar results were also reported in palm oils collected from Malaysia , and Spain . Furthermore, blended oils containing palm oil were also accompanied by greater levels of MCPD esters and glycidyl esters (GEs) against other oils .…”
Section: Recent Occurrences In Foodstuffssupporting
confidence: 79%
“…Similar results were also reported in palm oils collected from Malaysia , and Spain . Furthermore, blended oils containing palm oil were also accompanied by greater levels of MCPD esters and glycidyl esters (GEs) against other oils . These differences among the oil categories might be due to different intrinsic compositions of the raw materials. , Diversities of chlorine contents in different crude oils (4000–6000 μg/kg) were considered to be another possible reason for the difference of 3-MCPD ester contents .…”
Section: Recent Occurrences In Foodstuffssupporting
confidence: 69%
See 1 more Smart Citation
“…However, palm oil is still one of the most suitable edible oils for frying, and it is favoured by the user due to its stability against oxidation. With all the efforts from food safety authorities and industries worldwide, the level of MCPD esters and GE in palm oil and related products are controlled in general ( Abd Razak et al, 2019 ; Ramli et al, 2020 ). Temperature …”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, profound changes in fat occur, accompanied by the accumulation of toxic fat oxidation products that affect the human body. The migration of thermally modified fats into a product and their thermal modification are studied by scientists, however, taking into account new studies [8], safety indicators are not fully identified and regulated at the legislative level.…”
Section: Introductionmentioning
confidence: 99%